The Need for New Service Innovation in Halal Marketing - Kabiraj, Sajal; Walke, R. C.; Yousaf, Salman (Indian Journal of Marketing, 2014)
Purpose: Global halal food trade is estimated to be 700 billion (USD) and is expected to grow at the rate of 7% annually. Also, quality certifications and high quality standards have improved the product acceptability to a larger extent. The paper intends to analyze the opportunities and challenges of halal products. Design /Approach: The primary focus of this paper is to provide a better understanding of the concept of "Halal" and application of the overall approach and concept practice in the community. Findings and Social Implications: The paper intends to understand the importance of halal food in the halal market and understand the growth trajectory of halal products in both Muslim and non-Muslim population worldwide due to the increasing awareness and accessibility to information, which is affecting the global halal product demand. Also, halal accreditation is an effective tool to monitor halal products in the market as well as supervising their production during storage and transportation. The time period of the study was between 2010 and 2012. Practical Implications: More than 25 countries established halal authority for achieving halal standards according to the halal requirements. Various countries are developing competitiveness for halal products and are extending growth through exports. Originality/Value: This paper tries to develop an understanding on halal marketing and analyses opportunities and challenges for halal products and the halal industry so as to improve competitiveness and industrial development.